تطبيق نموذج التعليم القائم على المشاريع أوProject Based Learning في تعلماللغة العربية في المدرسة المتوسطة الإسلامية الحكومية 5 باسامان - Herita Natasya; Nurhasnah Nurhasnah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
The researching in this thesis was motivated by the existence of problems with student at mtsn 5 pasaman Students realize that in teaching this language students will not be interested in learning Arabic if they do not use an approach or model in their learning, Not all students actively participate in this project-based learning model, Lack of resources such as textbooks and technology in implementing the project-basedlearning model ,Difficulty in time management, because project-based learning requires time for planning, implementation. The research methodology studied by researchers used qualitative methods. The qualitative method is research that attempts to reveal the natural or realistic conditions that exist at that location. Qualitative research not only collects individual variables, but these variables can be linked to other variables. This research, the researcher used a qualitative approach with a descriptive case study type, namely research that describes a social event and certain situations that are described correctly using words. Results show that the challenges of the project-based learning model process: learning Arabic through a project-based model at SMP Islam Negeri 5 Pasaman faces many challenges, including: The diversity of students' basic abilities middle school students have varying knowledge and abilities in Arabic. Difficulty in time management .The time allocated for learning Arabic at SMP Negeri 5 Basaman is generally limited, so it can be a challenge to complete projects that take a long time because project-based learning requires time for planning, implementation and evaluation, Availability of learning resources.